UKRAINIAN DATABASE AND ATLAS OF LIGHT CURVES OF ARTIFICIAL SPACE OBJECTS - Koshkin, N. I.; Savanevich, V.; Pohorelov, A.; Shakun, L.; Zhukov, V.; Korobeynikova, E.; Strakhova, S.; Moskalenko, S.; Kashuba, V.; Krasnoshchokov, A. (Одеські астрономічні публікації, 2017)
This  paper  describes  the  Ukrainian database  of  long-term  photometric  observations  of resident  space  objects  (RSO).  For  the  purpose  of  using this  database  for  the  outer  space  monitoring  and  space situational awareness (SSA) the open internet resource has been developed. The paper shows examples of using the Atlas  of  light  curves  of  RSO's  for  analyzing  the  state  of rotation  around  the  center  of  mass  of  several  active  and non-functioning satellites in orbit.